Conversion of spoiled eggs into high-quality fertilizer using microbial inoculants and their effects on growth and yield of water spinach (Ipomoea aquatica) - Phan, Thi Thuy; Pham, Thanh Dat; Duong, Duc Trung; Vu, Nguyen Thai Ha; Vu, Huyen Thuong; Le, Thi Trang; Do, Thi Huong (Hue University Journal of Science: Natural Science, 2025)
Converting agricultural waste into value-added products is a sustainable strategy to reduce environmental pollution and enhances resource efficiency. This study evaluated the effectiveness of three microbial inoculants—EMZEO, EMUNIV, and EMIC—in composting spoiled eggs into high-quality fertilizers and assessed their effects on the growth and yield of water spinach (Ipomoea aquatica). Egg fertilizers produced using these inoculants (EFs) were compared with a commercial Organic Fish fertilizer in a randomized complete block design with three replications. Nutrient analysis showed that EF‑EMUNIV had the highest levels of nitrogen (1.25%), phosphorus (0.94%), potassium (6.13%), and calcium (1.35%), followed by EF‑EMIC (1.23%, 0.75%, 5.92%, 1.25%) and EF‑EMZEO (1.20%, 0.63%, 5.52%, 0.75%). Microbiological tests confirmed that all fertilizers were free from Escherichia coli and Salmonella spp., indicating their safety for agricultural use. EF‑EMUNIV significantly improved plant growth indicators such as shoot length, leaf number, and SPAD value, and produced the highest yield (7.74 t ha⁻¹), comparable to Organic Fish (7.41 t ha⁻¹) and EF‑EMIC (7.23 t ha⁻¹). Nitrate concentrations in all treatments ranged from 120.3 to 149.7 mg kg⁻¹, remaining within safe limits for leafy vegetables. Pearson correlation analysis revealed strong associations between yield and branch number (r = 0.895**), SPAD (r = 0.789**), leaf number (r = 0.748**), and leaf area index (r = 0.701**). The findings highlight the potential of EMUNIV as the most effective inoculant for converting spoiled eggs into safe and efficient fertilizers for leafy vegetable production.